The history of emotions an introduction - Plamper, Jan, 1970- (Oxford, United Kingdom : Oxford University Press, 2015)
The history of emotions is one of the fastest growing fields in current historical debate, and this is the first book-length introduction to the field, synthesizing the current research, and offering direction for future study. This book is organized around the debate between social constructivist and universalist theories of emotion that has shaped most emotions research in a variety of disciplines for more than a hundred years: social constructivists believe that emotions are largely learned and subject to historical change, while universalists insist on the timelessness and pan-culturalism of emotions. In historicizing and problematizing this binary, Jan Plamper opens emotions research beyond constructivism and universalism; he also maps a vast terrain of thought about feelings in anthropology, philosophy, sociology, linguistics, art history, political science, the life sciences - from nineteenth-century experimental psychology to the latest affective neuroscience - and history, from ancient times to the present day.
Includes bibliographical references (pages 309-341) and index.
Keywords: Emotions -- History; Emotions (Philosophy); Emotions; Emotions (Philosophy); History